A study of deep well disposal of desalination brine waste - LeGros, P. G. (United States Department of the Interior / Washington, 1969)
An increasing number of united states communities are being forced to seek additional potable water and are finding insufficient resources of good quality water to supply the demand. Desalination of brackish water is, in many cases the most economical method of extending water resources to supply these increasing demands. A byproduct of any desalination process is the waste stream, consisting of a concentrated solution of the soluble salts contained in the saline feed. The concentration of the dissolved solids in the waste stream depends upon both the composition of the brackish water feed and the desalination process